The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s11632-008-0025-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NaCl on growth and ion relations in two salt-tolerant strains of Paxillus involutus

Abstract: The effect of NaCl on growth, biomass and ion relations of two salt-tolerant isolates of Paxillus involutus, MAJ and NAU were investigated. The two Paxillus strains were exposed to the following concentrations of NaCl: 0, 100, 200 and 500 mmol·L -1 . Growth of MAJ and NAU was enhanced by 100 mmol·L -1 NaCl but severely inhibited at the concentration of 500 mmol·L -1 . NAU exhibited a greater capacity to exclude Na + and Cl -under all salinity levels, whereas the salt-includer MAJ had a higher capacity in nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Mycorrhizal symbiosis has been proposed as a key factor for better salt tolerance of woody species by reducing Na uptake (Guerrero-Galán et al 2019). While high salinity imposes Na toxicity and reduces fungal growth, mild-moderate Na occurrence has been reported to stimulate the growth of some mycorrhizal species (Bois et al 2006;Matsuda et al 2006;Zhang et al 2008), which may contribute to the positive correlations between soil Na and mycorrhizal biomass. However, the mechanisms driving mycorrhizal biomass responses to salinity variation are not known, and the effects of salinity on mycorrhizal-related processes need further investigation.…”
Section: Soil Salinity May Mediate Variation In Totaland Mycorrhizal Fungal Biomassmentioning
confidence: 99%
“…Mycorrhizal symbiosis has been proposed as a key factor for better salt tolerance of woody species by reducing Na uptake (Guerrero-Galán et al 2019). While high salinity imposes Na toxicity and reduces fungal growth, mild-moderate Na occurrence has been reported to stimulate the growth of some mycorrhizal species (Bois et al 2006;Matsuda et al 2006;Zhang et al 2008), which may contribute to the positive correlations between soil Na and mycorrhizal biomass. However, the mechanisms driving mycorrhizal biomass responses to salinity variation are not known, and the effects of salinity on mycorrhizal-related processes need further investigation.…”
Section: Soil Salinity May Mediate Variation In Totaland Mycorrhizal Fungal Biomassmentioning
confidence: 99%
“…[See online article for color version of this figure. ] in the maintenance of K + homeostasis by delivering the nutrient to the plant and slowing the loss of K + under NaCl stress. Zhang et al (2008) reported that P. involutus mycelium, especially strain MAJ, increased the uptake of K + after exposure to salt treatment. Salt shock caused an instantaneous influx of K + into the fungal mycelium; however, ST-and LT-stressed hyphae exhibited a K + efflux (Fig.…”
Section: Em Ameliorates K + Homeostasismentioning
confidence: 99%
“…Paxillus involutus strains MAJ and NAU have been identified as highly salt-tolerant fungi (Gafur et al, 2004;Langenfeld-Heyser et al, 2007;Zhang et al, 2008). Colonization with P. involutus strain MAJ reduces the buildup of Na + but enhances K + accumulation in the leaves of a salt-sensitive hybrid poplar, Populus 3 canescens (Langenfeld-Heyser et al, 2007, Luo et al, 2011.…”
Section: Salt-induced Fluxes Of Hmentioning
confidence: 99%
“…or Laccaria sp. (Hutchison 1990;Kernaghan et al 2002), and of isolates of the same species as Paxillus involutus (Zhang et al 2008), Suillus spp. (Hutchison 1990;Dixon et al 1993;Bois et al 2006a;Tang et al 2009;Obase et al 2010), and Pisolithus sp.…”
Section: Soil Fungi Differ Greatly In Their Behaviour In Saline Environmentsmentioning
confidence: 99%
“…In all cases, ion toxicity seems to be responsible for most of the negative effects observed on fungal growth, compared to the osmotic component due to the abundance of solutes in the environment (Dixon et al 1993;Chen et al 2001;Kernaghan et al 2002;Bois et al 2006a). Also, some ectomycorrhizal fungi seem to have evolved towards salt tolerance and their growth can even be stimulated by the application of moderate NaCl concentrations in the range of 25-50 mM (Dixon 1993;Bois et al 2006a;Matsuda et al 2006) or higher (Zhang et al 2008;Obase et al 2010). Recent studies using genomic techniques, have detected how populations of the ectomycorrhizal fungus Suillus brevipes in North America are able to adapt to stress associated with climate regimes and abiotic environments (Branco et al 2015(Branco et al , 2017.…”
Section: Soil Fungi Differ Greatly In Their Behaviour In Saline Environmentsmentioning
confidence: 99%